Towns without a contado. Building urban territoriality in Friuli (13th-15th century) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
A recent revival has broken away from more traditional doubts about the degree of territoriality of ‘premodern’ polities. Studies in the political culture of the Italian communes have shown that the latter thought and acted with some degree of territoriality in mind. By combining fruitfully traditional institutional studies and the so-called spatial turn scholars are now focusing on bundles of practices, spaces and representations as a way to unpack ‘premodern’ territoriality.With this contribution I will try to refute some common narrations on pre-venetian Friuli, whose towns and urban centres were able to build and conceive their own substantially autonomous political spaces even within the framework of an ecclesiastical principality. By analysing both official and private sources I will argue that a town like Udine managed to build and enforce a clearly defined territory by pivoting and exploiting the extensive lands owned by its citizens. GIS methodology will be key in understanding the chronology and topography of the political expansion of Udine in its ‘unofficial’ contado.
Keywords: communes; North-eastern Italy; 13th-15th century; territoriality; landed property